(untitled) (Research, Society and Development, 2020)
The objective was to know the experiences of transgender people in health care from. This is a systematic review followed by a qualitative meta-synthesis carried out between. It was searched between May and June 2019, in the databases Pubmed, LILACS and SciELO. Six scientific articles were included in Portuguese, English or Spanish; published between 2009 and 2018. A for qualitative meta-synthesis consisted of six articles and in the analysis; showing the attention to the health of the trans person and the body and psyche of the trans person. Regarding the health care of the trans person, it was identified that there is a lack of referral health services, a long waiting time to start hormone therapy and / or sex reassignment surgery and the search for other countries to speed up body modification processes. As for health professionals. There was also difficulty in handling the trans adolescent, prejudice and empathy, disrespect to the social name and pathologization of transgender. In relation to the trans body, the strategies used for the recognition of transidentity, the. In relation to psychosocial aspects, psychiatric health and isolation or maintenance of the condition in secret for fear of discrimination were evidenced. It is suggested to invest in the training of health professionals in meeting trans-specificities.